Superior energy-storage density and ultrahigh efficiency in KNN-based ferroelectric ceramics via high-entropy design - Yu Huan; Lingzhi Wu; Luoyuan Xu; Peng Li; Tao Wei (Journal of Materiomics)
The rapidly advancing energy storage performance of dielectric ceramics capacitors have garnered significant interest for applications in fast charge/discharge and high-power electronic techniques. Simultaneously improving the recoverable energy storage density Wrec and efficiency η becomes more prominent at the present time for their practical applications. Herein, a high-entropy concept is implemented on the (K0·5Na0.5)NbO3 (KNN)-based ferroelectric ceramics to design the high-performance dielectric capacitors. First, the strong lattice distortion can absorb some electric energy during the electrical loading process and result in the delayed polarization saturation. Additionally, the large composition fluctuations induce the weak correlation between polar nanoregions and enhance the η. Finally, the high-entropy design and viscous polymer processing method reduce the grain size and improve the Eb. In consequence, excellent Wrec of 11.14 J/cm3 with high η of 87.1% are achieved under an electric field of 750 kV/cm in the high-entropy component. These results demonstrate that the high-entropy concept is a potential avenue to design the KNN-based high-performance dielectric energy storage capacitors.